Mixed Methods Research: Trends and Issues in Research Methodology - Rian Vebrianto; Musa Thahir; Zelly Putriani; Ira Mahartika; Aldeva Ilhami; Diniya (Bedelau: Journal of Education and Learning, 2020)
Mixed methods research is currently developing and has become an interesting issue and trend in the field of education. This makes the writers want to provide a reference and technical guidance to increase students' knowledge in providing mixed methods research. This type of research is literature review research that discusses various interesting issues from journals and books related to this research theme. This article describes matters related to the definition, types and procedures of mixed methods, population and samples, instruments, data collection and data analysis techniques carried out by mixed methods. The results of this study provide clarity and important exposure to research methodologies for students who will carry out their research in the field of education that focuses on mixed methods research. Hence, the research method will provide advantages of both quantitative and qualitative approaches to unveil the research phenomena in depth. In addition, this research has also real implications for students and researchers in carrying out good and appropriate mixed methods research.